Markups and inflation cyclicality in the euro area - Omiros Kouvavas; Chiara Osbat; Timo Reinelt; Isabel Vansteenkiste (European Central Bank (ECB), 2021)
Price inflation in the euro area has been stable and low since the Global Financial Crisis, despite notable changes in output and unemployment. We show that an increasing share of high markup firms is part of the explanation of why inflation remained stubbornly stable and low in the euro area over the past two decades. For this purpose, we exploit a rich firm-level database to show that over the period 1995-2018 the aggregate markup in the euro area has been on the rise, mainly on account of a reallocation towards high-markup firms. We document significant heterogeneity in markups across sectors and countries and, by linking these markup developments to the evolution of sectoral level producer and consumer price inflation, we find that (i) inflation in high-markup sectors tends to be less volatile than in low-markup sectors and (ii) inflation in high-markup sectors responds significantly less to oil supply, global demand and euro area monetary policy shocks.
Keywords: D2; D4; N1; O3; 330; Inflation; Price setting; Firm markups